Arts and culture in global development practice : expression, identity and empowerment - Maguire, Cindy; Holt, Ann (Art educator) (New York, NY : Routledge, 2022)
"This book explores the role that arts and culture can play in supporting global international development. The book argues that arts and culture are fundamental to human development, and can bring considerable positive results for helping to empower communities and provide new ways of looking at social transformation. Whilst most literature addresses culture in abstract terms, this book focuses on practice-based, collective, community-focused, sustainability-minded, and capacity-building examples of arts and development. The book draws on case studies from around the world, investigating the different ways practitioners are imagining or defining the role of arts and culture in Belize, Canada, China, Ethiopia, Guatemala, India, Kosovo, Malawi, Mexico, Peru, South Africa, Sri Lanka, Taiwan, Thailand, USA, and Western Sahara refugee camps in Algeria. The book highlights the importance of situated practice, asking what questions or concerns practitioners have, inviting a dialogic sharing of resources and possibilities across different contexts. Seeking to highlight practices and conversations outside normative frameworks of understanding, this book will be a breath of fresh air to practitioners, policy makers, students and researchers from across the fields of global development, social work, art therapy, and visual and performing arts education"--
Keywords: Community development -- Case studies; Social change -- Case studies; Arts -- Case studies; Culture -- Case studies; ART / Popular Culture; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Third World Development